2019
DOI: 10.1096/fj.201901950r
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced HE4 in tubular epithelial cells promotes extracellular matrix accumulation and renal fibrosis via NF‐κB

Abstract: Hypoxia-induced extracellular matrix (ECM) deposition is an important cause of renal fibrosis that is triggered by unknown mechanisms. Human epididymis secretory protein 4 (HE4) is a newly discovered key molecule that causes ECM deposition. We used the unilateral ureteral obstruction (UUO) mouse model to investigate the expression and mechanisms of HE4 in the pathogenesis of renal fibrosis. Results were confirmed in the HK2 cell line and in human donors of kidney tissue with chronic kidney disease. Hypoxia sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…RF is characterized by the proliferation of interstitial fibroblasts, excessive deposition of extracellular matrix (ECM), and renal tubular atrophy [ 4 ]. Transforming growth factor-β (TGF-β) is an important growth factor that activates its downstream regulatory factor Smad protein.…”
Section: Introductionmentioning
confidence: 99%
“…RF is characterized by the proliferation of interstitial fibroblasts, excessive deposition of extracellular matrix (ECM), and renal tubular atrophy [ 4 ]. Transforming growth factor-β (TGF-β) is an important growth factor that activates its downstream regulatory factor Smad protein.…”
Section: Introductionmentioning
confidence: 99%
“…This study also aimed to address how the expression of HE4 in the renal cortex affected the poor prognosis of RCC patients. Although the exact physiological and pathological functions of HE4 are poorly understood for several cancers and renal brosis, Zhang et al investigated the expression and mechanisms of HE4 in the pathogenesis of renal brosis by using the unilateral ureteral obstruction mouse model [16]. They found that hypoxia signi cantly increased HE4 expression in renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of HE4 in normal cortex can represent not only the onset of renal brosis but also EMT in RCC, which is a key process that promotes cancer invasion, distal metastasis and drug resistance [18]. Additionally, Zhang et al suggested HE4 in renal tubular epithelial cells was upregulated by hypoxia [15]. The tubular epithelial cells in normal cortex coexisting with RCC requiring blood supply is speculated to be under the hypoxic condition due to deprivation of blood ow.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum HE4 levels were found to be signi cantly increased in the early stages of CKD, and serum levels were also found to be correlated with the degree of renal brosis, suggesting that the upregulated expression of HE4 may present as one of the initial sign in the onset and progression of renal brosis [14]. Zhang et al investigated the expression and mechanisms of HE4 in the pathogenesis of renal brosis by using the unilateral ureteral obstruction mouse model [15]. They found that hypoxia signi cantly increased HE4 expression in renal tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%